Politics, subjectivity and the public/private distinction - Panton, J (2010)
A critical investigation of the public/private distinction as it has been conceived in Anglo-American political thinking in the second half of the 20th century. A broadly held consensus has developed amongst many theorists that public/private does not refer to any single determinate distinction or relationship but rather to an often ambiguous range of related but analytically distinct conceptual oppositions. The argument of this thesis is that if we approach public/private in the search for analytic or conceptual clarity then this consensus is correct. Against this I propose that a number of the most dominant invocations of the distinction can be understood to express public/private as an irreducibly political dialectic that mediates the relationship between the subjective and objective side of social and political life. By locating these conceptually diverse invocations within a broader and more determinate framework of the historical development and contestation of the boundaries which establish the conditions for subjectivity, as the assertion of political agency, on the one hand, and which demarcate, police and defend these particular boundaries, as part of the objectively given character of social life and institutional organisation, on the other hand, then a more determinate character to public/private can be recognized. I then seek to explore the capacity of this model to capture and explain the peculiar post-war problematisation of public/private amongst a number of new left thinkers in Britain and America.